Eating and lifestyle habits and primary school health-related programs: a survey involving Italian children and teachers - Acito, Mattia; Cangelosi, Giovanni; Petrelli, Fabio; Moretti, Massimo; Villarini, Milena; Celestino, Anna; Sordoni, Eleonora; Grappasonni, Iolanda (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Childhood overweight and obesity represent serious public health concerns in several countries worldwide, including Italy, where the highest prevalence in Europe of overweight and obesity among primary school children was recorded. Among others, primary schools represent suitable social environments for health education projects. In this perspective, to optimize resources and plan successful activities, it is necessary, first of all, to analyze the context of the intervention. Study design. A pilot survey involving children and teachers was conducted in a primary school in Jesi (Le Marche Region, Italy). Methods. A questionnaire was submitted by teachers between May and June 2023 to 104 pupils (aged 6–11) from the five different primary school system classes. A qualitative questionnaire was also filled out by the same teachers (n = 5) who were present while the children were filling the eating/lifestyle questionnaire. Results. Most of the children (96.1%) had breakfast before school, with milk and cereal (51.5%) representing the preferred combination. During recess, 59.2% of pupils usually have a sandwich, 23.3% usually have sweet snacks, whereas only 2.9% have a fruit. Over 55% of the sample preferred drinking high-sugar beverages to water, and 15.5% declared going to a fast-food restaurant more than once a week. Over 17% of children did sport only once a week or less often. Over 64% of children habitually played videogames, and 77.6% normally watched TV or played with a tablet/smartphone while eating. Finally, the teachers’ interview highlighted that there were no active health-related projects addressed to the pupils, and the school did not normally organize meetings with health professionals to increase children’s and their parents’ knowledge and awareness about healthy eating habits. Conclusions. This preliminary investigation analyzed the context for a future health and nutrition education project and will assist researchers in planning successful activities and increasing the efficiency of the intervention.